Analisis Semantik Kata Fitnah dalam Surah Al-Baqarah Ayat 191 Perspektif Imam At-Thobari dalam Tafsir Jami’ Al-Bayan Fi Ta’wil Ayi Al-Qur’an - Azhari, Zulheri; Ahmad Zuhri (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This study aims to analyse the semantic meaning of the word fitnah contained in Surah Al-Baqarah verse 191 by using Imam At-Thobari's tafsir perspective in his work, Jami' al-Bayan fi Ta'wil Ay al-Qur'an. A descriptive-analytical approach is used to explore Imam At-Thobari's understanding of the meaning of the word fitnah, by considering the root of the word (fi'tan), its use in various Qur'anic contexts, and its relevance to the socio-religious situation in the early days of Islam. The results show that the word fitnah has a complex and multidimensional meaning that includes trials, torture, oppression, chaos, deviation of faith, and actions that threaten the stability of faith and society. In the context of Surah Al-Baqarah verse 191, Imam At-Thobari explained that fitnah refers to disbelief, oppression of Muslims, and systematic efforts made by the polytheists of Quraysh to obstruct the preaching of Islam in Makkah before the hijrah. Furthermore, this study confirms that the understanding of the word fitnah cannot be separated from the historical context and social dynamics at the time of revelation. This finding not only enriches the treasures of Qur'anic interpretation but also provides a relevant perspective for Muslims in understanding contemporary challenges related to tests of faith, oppression, and social conflict. Thus, this research contributes to broadening the understanding of the meaning of the Qur'ān and its application in people's lives in various times.